1143–1147: Otto of Freising Identifies Baghdad and Cairo with Old and New Babylon (Transmediterranean History, 2023)
The article focuses on the depiction of Babylon in the Historia de duabus civitatibus by Otto, bishop of Freising (sed. 1138–1158). Otto uses this toponym to refer to the Mesopotamian city known from the Bible, but also to ʿAbbāsid Baghdad and Fāṭimid Cairo. To write these passages, Otto mainly relied on topographical knowledge of biblical, ancient, and patristic provenance. These he enriched selectively with contemporary knowledge, which he probably acquired from informants residing in the Latin East. Otto tried to convert these different pieces of information into a coherent narrative with Babylon at the centre. Otto’s comments make clear that the elite of the Staufen became increasingly interested in Muslim-ruled Egypt in the context of the Second Crusade. As opposed to later Staufen reporters such as Burchard of Strasbourg, however, Otto was apparently not yet able to acquire enough current information about this country.
Keywords: Babylon; Baghdad; Cairo; Hohenstaufen Dynasty; Bible; geography; knowledge transfer; images of the other; Egypt; Ayyubids; Fatimids